The Demand for Season of Birth - Clarke, D (John Wiley and Sons Ltd, 2019)
We study the determinants of season of birth for married women aged 20–45 in the USA, using birth certificate and Census data. We also elicit the willingness to pay for season of birth through discrete-choice experiments implemented on the Amazon Mechanical Turk platform. We document that the probability of a spring first birth is significantly related to mother s age, education, race, ethnicity, smoking status during pregnancy, receiving WIC (Women, Infants & Children) food benefits during pregnancy, prepregnancy obesity, and the mother working in “education, training, and library” occupations; whereas among unmarried women without a father acknowledged on their child s birth certificate, all our findings are muted. A summer first birth does not depend on socioeconomic characteristics, although it is the most common birth season in the USA. Among married women aged 20–45, we estimate the average marginal willingness to pay (WTP) for a spring birth to be 877 USD. This implies a willingness to trade-off 560 grams of birth weight in the normal range to achieve a spring birth. Finally, we estimate that an increase of 1,000 USD in the predicted marginal WTP for a spring birth is associated with a 15 pp (percentage points) increase in the probability of obtaining an actual spring birth. © 2019 The Authors Journal of Applied Econometrics Published by John Wiley & Sons Ltd